Acute motor axonal neuropathy following SARS-CoV-2 infection in the third trimester of pregnancy. Issue 6 (2nd November 2022) - Mohamed, Mohamed M. G.; Jadhav, Amar; Banuelos, Polo; Lacasse, Alexandre; Kumar, Vikas
Abstract: Neurological complications following SARS-CoV-2 infections are increasingly recognized. Despite that, sequelae from SARS-CoV-2 infection in gravid women are uncommonly reported. We present a case of acute motor axonal neuropathy, a variant of Guillain-Barre syndrome, in a 26-year-old primigravida at 34 weeks' gestation. She presented with worsening diplopia, dysphagia, and lower extremity sensory and motor deficits after testing positive for SARS-CoV-2 2 weeks earlier. Due to rapidly progressive symptoms, she required endotracheal intubation and mechanical ventilation. Initially she was diagnosed with Miller Fisher syndrome, but serology and electromyography studies were consistent with acute motor axonal neuropathy. Spontaneous preterm delivery, supportive care, and intravenous immunoglobulin therapy resulted in clinical improvement. Steady recovery was achieved by a prolonged rehabilitation program.